An Ordinary Differential Equation Model for Simulating Local-pH Change at Electrochemical Interfaces - Mukouyama, Yoshiharu; Nakanishi, Shuji (Frontiers in Energy Research, 2020)
The local pH value at an electrochemical interface (pHs) inevitably changes during redox reactions involving the transfer of H+ or OH- ions. It is important to quantitatively estimate pHs during polarization, as this parameter has a significant impact on the activity and selectivity of electrochemical reactions. Numerical simulation is an effective means of estimating pHs because it is not subject to experimental constraints. Typically, pHs is simulated by solving partial differential equations that describe diffusion. In the present work, we show that such electrochemical systems can also be described using ordinary differential equations, significantly reducing the computational resources required. In the work reported herein, this was achieved by considering the reaction plane in the diffusion layer over which the H+ and OH- concentrations are balanced while assuming a steady state. The resulting model successfully reproduces experimental voltammograms characterized by local pH changes in association with the hydrogen evolution and hydrogen peroxide reduction reactions.